Mitochondrial DNA damage and reactive oxygen species in neurodegenerative disease - Nissanka, Nadee; Moraes, Carlos T. (FEBS letters, 2018)
Mitochondria are essential organelles within the cell where most ATP is produced through oxidative phosphorylation (OXPHOS). A subset of the genes needed for this process are encoded by the mitochondrial DNA (mtDNA). One consequence of OXPHOS is the production of mitochondrial reactive oxygen species (ROS), whose role in mediating cellular damage, particularly in damaging mtDNA during ageing, has been controversial. There are subsets of neurons that appear to be more sensitive to ROS‐induced damage, and mitochondrial dysfunction has been associated with several neurodegenerative disorders. In this review, we will discuss the current knowledge in the field of mtDNA and neurodegeneration, the debate about ROS as a pathological or beneficial contributor to neuronal function, bona fide mtDNA diseases, and insights from mouse models of mtDNA defects affecting the central nervous system.